Elicitation of Stilbenes and Benzofuran Derivatives in Hairy Root Cultures of White Mulberry (Morus alba) - Lingling Fang; Amit Raj Sharma; Chineche Aniemena; Krystian Roedel; Florence Henry; Philippe Moussou; Anita Samuga; Fabricio Medina-Bolivar (Plants, 2022)
Stilbene and benzofuran derivatives isolated from the root of white mulberry (Morus alba) have shown various biological activities, including anti-inflammatory, antioxidant, and antimicrobial properties. The objectives of this study were to develop hairy root cultures and assess the effect of multiple elicitors combinations including (I) methyl-β-cyclodextrin (CD), MgCl2, methyl jasmonate (MeJA), and H2O2, (II) CD, MgCl2, and MeJA and (III) CD, MgCl2, and H2O2, on the production of these bioactive compounds. The highest yields of stilbenes and benzofurans were obtained upon co-treatment with 18 g/L CD, 3 mM H2O2 and 1 mM MgCl2. The stilbenes oxyresveratrol, resveratrol, and 3′-prenylresveratrol accumulated up to 6.27, 0.61, and 5.00 mg/g DW root, respectively. Meanwhile, the aryl benzofurans moracin M and moracin C accumulated up to 7.82 and 1.82 mg/g DW root, respectively. These stilbenes and benzofurans accumulated in the culture medium of the elicited hairy root cultures. They were not detected in the root tissue. However, the oxyresveratrol diglucoside mulberroside A was only detected in the root tissue with yields up to 10.01 mg/g DW. The results demonstrated that co-treatment of white mulberry hairy root cultures with multiple elicitors can significantly enhance production and secretion of stilbenes and benzofurans in this controlled and sustainable axenic culture system.